Interpretação dos significados atribuídos à instituição escolar pelo povo Rikbaktsa - Martins, Anderson (2018)
This research offers a panoramic view of the Rikbaktsa community, bringing to the fore some aspects related to its school trajectory, in order to identify the meanings attributed by this group to its schooling process. In order to fulfill this purpose, we resort to various methodological resources, such as literature review and interviews with members of that community, targeting primarily those in the educational field. The first part of our work consists of a brief presentation of the said people, describing it in its general aspects, such as: language, territories, inter-ethnic conflicts, etc. The second chapter seeks to investigate how their passage through Utiariti boarding school took place and how such an experience would impact the lives of those individuals. In the third part of the dissertation, we proceed to a more "ethnographic" analysis in order to identify the way the school institution is conceived by the Rikbaktsa, considering whether there the various experiences that marked its process of approximation with the respective proposal of teaching. In our final remarks, we observe that the school has assumed different meanings in the life of that people, being assimilated initially as an instrument of cultural homogenization to be taken more recently in a space of affirmation of their customs, values and traditional knowledge.